A primary estimation of PCDD/Fs release reduction from non-wood pulp and paper industry in China based on the investigation of pulp bleaching with chlorine converting to chlorine dioxide. (October 2017) - Xiao, Qingcong; Song, Xiaoqian; Li, Wenchao; Zhang, Yuanna; Wang, Hongchen
Abstract: Chlorine bleaching technology (C process, CEH process, H process and theirs combination), which was identified as a primary formation source of PCDD/Fs, is still widely used by the vast majority of Chinese non-wood pulp and paper mills (non-wood PMs). The purpose of this study was to provide information and data support for further eliminating dioxin for non-wood PMs in China, and especially to evaluate the PCDD/Fs release reduction for those mills converting their pulp bleaching processes from CEH to ECF. The PCDD/Fs concentrations of the bleached pulp and bleaching wastewater with ECF bleaching were in the ranges of 0.13–0.8 ng TEQ kg −1, and 0.15–1.9 pg TEQ L −1, respectively, which were far lower than those with CEH process, indicating that the ECF process is an effective alternative bleaching technology to replace CEH in Chinese non-wood PMs to reduce dioxin release. The release factor via flue gas of the alkali recovery boiler in Chinese non-wood PMs was first reported to be 0.092 μg TEQ Ad t −1 in this study. On the assumption that pulp bleaching processes of all Chinese non-wood PMs were converted from CEH to ECF, the annual release of PCDD/Fs via the bleaching wastewater and bleached pulp would be reduced by 79.1%, with a total of 1.60 g TEQ. Highlights: The levels and mass distributions of PCDD/Fs between pulp bleaching with chlorine and chlorine dioxide were compared. The release factor via flue gas of the alkali recovery boiler in Chinese non-wood pulp was first reported. The PCDD/Fs release reduction in Chinese non-wood pulp and paper industry was estimated with pulp bleaching from CEH to ECF. Efforts should be further devoted to update PCDD/F toolkit.